2000
DOI: 10.1017/s0022112099008125
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent kinetic energy transport in a corner formed by a solid wall and a free surface

Abstract: High-resolution DPIV and LDV measurements were made in a turbulent mixed- boundary corner, i.e. a turbulent boundary layer generated by horizontal flow of water along a vertical wall in the vicinity of a horizontal free surface. This work is an extension of an earlier numerical/experimental study which established the existence of inner and outer secondary flow regions in the corner. The inner secondary motion is characterized by a weak, slowly evolving vortex with negative streamwise vorticity. The outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 15 publications
5
57
1
1
Order By: Relevance
“…This issue will be discussed later based on the Reynolds-stress budget data. A difference between the results of the present work and those of Hsu et al (2000) is that the recovery of u u occurs across almost all the surface, except at the lower-wall bisector where ∂ u /∂y is equal to zero and ∂ u /∂z values are almost constant in the region 0.8 < z/D < 1. Previous studies of Perot & Moin (1995) and Walker et al (1996) revealed significant differences between shear-free boundary layers near solid walls and free surfaces, such as the higher tangential Reynolds stress and lower dissipation near a free surface.…”
Section: Open Duct: Reynolds Stressescontrasting
confidence: 90%
See 3 more Smart Citations
“…This issue will be discussed later based on the Reynolds-stress budget data. A difference between the results of the present work and those of Hsu et al (2000) is that the recovery of u u occurs across almost all the surface, except at the lower-wall bisector where ∂ u /∂y is equal to zero and ∂ u /∂z values are almost constant in the region 0.8 < z/D < 1. Previous studies of Perot & Moin (1995) and Walker et al (1996) revealed significant differences between shear-free boundary layers near solid walls and free surfaces, such as the higher tangential Reynolds stress and lower dissipation near a free surface.…”
Section: Open Duct: Reynolds Stressescontrasting
confidence: 90%
“…All terms contribute to the budgets of v v and w w . Hsu et al (2000), observed that both TKE production and dissipation are dramatically reduced in the near-corner region, close to the free surface. Far from the wall, this results in an increase of the surface-parallel fluctuations very close to the free surface.…”
Section: Open Duct: Reynolds Stressesmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, Shah et al (1999Shah et al ( , 2000 have used highly resolved digital particle image velocimetry (DPIV) data to compute terms in the vorticity transport equation, along with turbulent strain rates in a turbulent tip vortex shed from a half D-wing. Hsu et al (2000) presented turbulent kinetic energy transport quantities obtained from DPIV measurements in a turbulent boundary layer.…”
Section: (A ) Experimental Data As Analytical Modelling Inputmentioning
confidence: 99%